Kirana Analisis Kesalahan Penggunaan Ejaan Bahasa Indonesia pada Artikel Mahasiswa Pendidikan Bahasa dan Sastra Indonesia Abulyatama Angkatan 2020: Studi kasus pada mahasiswa Program Studi Pendidikan Bahasa dan Sastra Indonesia - Sahlan, Kirana; Meri Yulizar,; Intan Munawarah, (Jurnal Serambi Ilmu, 2026)
This study was motivated by the phenomenon of the use of spelling that is not in accordance with the rules in student articles. The formulation of the problem in this study is how to use Indonesian spelling and what are the factors that cause spelling errors in articles of students of the Language Education Study Program and what are the factors that cause spelling errors in articles of students of Indonesian Language and Literature Education, Abulyatama University. The method used is a mixed method with a sequential explaratory design, namely collecting qualitative data first, followed by quantitative data. The results of the study showed that there were 642 spelling errors divided into 12 categories, including: use of capital letters, italics, punctuation (comma, period, colon, semicolon) hyphens, quotation marks, prepositions, standard vocabulary, use of question words, and ineffective sentences. The main factors that influence spelling errors are lack of understanding of EYD, low reading habits, and lack of revision and editing in writing articles.